Pop-Up Book Design as an Effective Tool for Promoting Creativity in the Eighth Grade Social Studies Learning - Pratiwi, Nanda; Irawan, Listyo Yudha (Institut Agama Islam Negeri Ponorogo, 2025)
Based on the results of observations conducted in class VIII D IPS SMP Bahrul Maghfiroh, it is known that the level of student creativity is still low. The low creativity is mainly caused by the learning method that is less interesting and the involvement of students actively and effectively. This study aims to apply Pop-Up Book learning media to improve student creativity. Pop-Up Book media was chosen because it has visual and interactive qualities that can stimulate learning interest and improve students' cognitive and affective development. This study uses the Research and Development (R&D) research method, by utilizing the 4D development model which includes the stages of Define, Design, Develop, and Disseminate. The results of the study showed that Pop-Up Book learning media was able to improve student creativity using the Project Based Learning (PjBL) approach. In the comparison of the results of cycles 1 and 2 of this study, there was a significant increase in student creativity. In cycle I, the average value of 64.17 increased to 84.17 in cycle II. Pop-Up Book media has proven to be a practical, interactive and innovative learning tool and functions to train and develop students' creativity in learning activities.